Growth and yield responses of radish (Raphanus sativus) to different types and doses of organic manures in mid-hill region of Uttarakhand - BHATT H; SINGH K C; PANT S C; HAOBIJAM J W; SERAM D; BHOSALE T A L; RATURI G (The Indian Journal of Agricultural Sciences)
The present study was carried out in 2021 at College of Horticulture, Veer Chandra Singh Garhwali Uttarakhand University of Horticulture and Forestry, Bharsar, Uttarakhand to investigate the response of radish to certain types and doses of organic manures under polyhouse condition. Twelve different treatment combinations, viz. T1 (Control); T2 (FYM 100%); T3 (Vermicompost 100%); T4 (Goat manure 100%); T5 (Neem cake 100%); T6 (FYM 50% + Vermicompost 50%); T7 (FYM 50% + Goat manure 50%); T8 (FYM 50% + Neem cake 50%); T9 (Vermicompost 50% + Goat manure 50%); T10 (Vermicompost 50% + Neem cake 50%); T11 (Goat manure 50% + Neem cake 50%); T12 (FYM 25% + Vermicompost 25% + Goat manure 25% + Neem cake 25%). The earliest initial germination (3.00 days) was seen in T4, maximum germination per cent (94.44%) in T6, greatest fresh biomass of leaves and roots/plant in T10 and T2 (182.26 g and 181.60 g, respectively) and the highest yield (20.180 t/ha) was also recorded in T2 resulting the highest cost-benefit ratio (1: 3.80). T3 provided highest TSS (4.23°B) and ascorbic acid (17.61 mg/100 g) and highest root dry matter (8.84 g/100 g) in T10. Among the treatments tested, T2 was found to be the best for obtaining the highest yield, highest net return, highest cost-benefit ratio, and also performed well in terms of quality and growth parameters in the temperate hilly regions of Uttarakhand. It can further be concluded that organic manures provided appreciable results in radish cultivation. Therefore, FYM @100% shall be recommended for the radish growers to derive maximum profits.